Warsini! Are you not tired standing in the factory? A Reflection on Women’s Labour Pedagogy - Tiwon, Sylvia (Yayasan Jurnal Perempuan, 2016)
This article is a reflection on feminist education at the complex intersection of feminism, the workers movement and the movement towards social transformation in Indonesia. It raises questions about the effectiveness of gender training programs that have become almost a prerequisite for programs and funding among many non-government organizations, national and international. The writerargues that the institutionalization of gender training has been dissociated from the movement for transformational justice and from the concrete experience of workers.